Free-standing 2D non-van der Waals antiferromagnetic hexagonal FeSe semiconductor: halide-assisted chemical synthesis and Fe²⁺ related magnetic transitions - Xu, Junjie (2022)
The scarcity of two-dimensional (2D) magnetic nanostructures has hindered their applications in spintronics, which is attributed to that most magnetic materials exhibit non-van der Waals (nvdWs) structures and it is hard to reduce their thickness to 2D nanostructures. Thus it is necessary to develop a promising strategy for free-standing 2D magnetic nvdWs nanostructures. We have achieved free-standing 2D nvdWs hexagonal FeSe with a thickness of 2.9 nm by the reaction between the oleylamine-Se complex and Fe2+ with the assistance of Cl-, where the synergetic effects of Cl- and -NH2 lead to anisotropic growth. Inspiringly, the 2D hexagonal FeSe exhibits intrinsic antiferromagnetic order rooted in Fe2+ and semiconducting nature. In addition, the temperature variation would result in the chemical environment changes of Fe2+, responsible for the temperature-dependent magnetic transitions. This work promotes the potential applications of 2D hexagonal FeSe and the preparation of other 2D nvdWs materials.